PENYULUHAN BUDIDAYA TANAMAN JAGUNG DI DESA KAIRATU KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Makaruku, Marlita H.; L. Tanasale, Vilma; Goo, Nureny (HIRONO : Jurnal Pengabdian Masyarakat, 2025)
Corn (Zea mays L.) is one of the main food crop commodities that has an important and strategic role in improving the Indonesian economy. The demand for maize is high and will increase as the population grows. Kairatu Village is one of the villages in Kairatu Sub-district that has the potential to develop corn cultivation. The problem faced by the partner farmer groups is the lack of knowledge on how to cultivate corn properly. The purpose of this community service activity is to increase community knowledge, both theoretically and practically, in implementing corn cultivation in Kairatu Village, Kairatu District, West Seram Regency. This community service activity was carried out through the following stages: preparation, counselling, making demonstration plots, and evaluating activities. The results obtained from the implementation of this PKM activity are that the community has increased knowledge about good corn cultivation.